Social Media Support and Funding Assistance for Psychological Injuries in Social Work - Hu, Xiaowu; Tang, Caiyi; Wang, Dongmei (Frontiers in Public Health, 2022)
Introduction Psychological injuries in social work are on the rise in complex modern society. Some individuals are incurring both physical and psychological injuries. Often, psychological injuries are more miserable than physical injuries. To combat the psychological injury suffered by individuals involved in social work, authorities should mobilize support via social media and raise funds by this and other feasible means to cover the cost of care for these individuals. This study focuses on social media support and funding assistance that could play useful roles in helping to treat psychological injuries among social workers and their clients in China. Methods A scoping review of academic and gray literature was undertaken to identify the different injuries involved in social work. Semi-structured interviews were carried out with 7 experts, including social workers, social media professionals, and social fund directors. Empirical studies on psychological injuries in social work provided examples in support of the policy advocacy reported in this paper. Results The scoping review found diverse literature on the subject of psychological injury in social work over the past decade in China. Semi-structured interviews with experts indicate that social media support can alleviate psychological suffering and that funding assistance has a positive influence on assisting individuals coping with psychological injuries. The empirical cases support the plan to encourage more support from social media and funding sources. Conclusion Psychological injury is greatly influenced by social bias and discrimination. According to cases and actions are taken to mitigate the harm done, supportive social media strategies could greatly diminish the psychological injuries to social workers and their clients and help them avoid much suffering. This study finds that funding organizations could provide a new treatment mechanism—social media marketing strategies and functional activities—to help a large number of individuals with psychological injuries out of the disease trap in China.